Neonatal intensive care parent satisfaction: a multicenter study translating and validating the Italian EMPATHIC-N questionnaire - Dall'Oglio, I.; Fiori, M.; Tiozzo, E.; Mascolo, R.; Portanova, A.; Gawronski, O.; Ragni, A.; Amadio, P.; Cocchieri, A.; Fida, R.; Alvaro, R.; Rocco, G.; et al. (2018)
Background: In Neonatal Intensive Care Units (NICUs), parent satisfaction and their experiences are fundamental to assess clinical practice and improve the quality of care delivered to infants and parents. Recently, a specific instrument, the EMpowerment of PArents in THe Intensive Care-Neonatology (EMPATHIC-N), has been developed in the Netherlands. This instrument investigated different domains of care in NICUs from a family-centered care perspective. In Italy, no rigorous instruments are available to evaluate parent satisfaction and experiences in NICU with family-centered care. The aim of this study was to translate and validate the EMPATHIC-N instrument into Italian language measuring parent satisfaction. Methods: A psychometric study was conducted in nine Italian NICUs. The hospitals were allocated across Italy: four in the North, four in Central region, one in the South. Parents whose infants were discharged from the Units were enrolled. Parents whose infants died were excluded. Results: Back-forward translation was conducted. Twelve parents reviewed the instrument to assess the cultural adaptation; none of the items fell below the cut-off of 80% agreement. A total of 186 parents of infants who were discharged from nine NICUs were invited to participate and 162 parents responded and returned the questionnaire (87%). The mean scores of the individual items varied between 4.3 and 5.9. Confirmatory factor analysis was performed and all factor loadings were statistically significant with the exception of item ‘Our cultural background was taken into account’. The items related to overall satisfaction showed a higher trend with mean values of 5.8 and 5.9. The Cronbach’s alpha’s (at domain level 0.73-0.92) and corrected item-total scale correlations revealed high reliability estimates. Conclusions: The Italian EMPATHIC-N showed to be a valid and reliable instrument measuring parent satisfaction in NICUs from a family-centered care perspective. Indeed, it had good psychometric properties, validity, and reliability. Furthermore, this instrument is fundamental for further research and internationally benchmarking.